Design, construction and performance testing of solar crop dryers for rural areas - Runganga, Tatenda B.; Kanyarusoke, Kant E. (Proceedings of the ... Conference on the Industrial and Commercial Use of Energy (Print), 2018)
Postharvest losses experienced by farmers in rural areas are mainly due to food degradation caused by high moisture content and poor initial moisture control. Farm drying methods often compound this problem by contaminating the produce with foreign matter. This paper describes a 'design, construct, test and cost' approach to tackle the problem at rural farm level. The basic assumption is rural farmers desire to reduce postharvest losses, and hence, need to adopt affordable low cost, low technology methods in controllably drying their produce. It was decided that enclosed solar crop drying was feasible due to the high solar radiation levels during harvest times. Therefore, two different dryers designs with 1.5m 2 and 2m 2 glazing area were designed, constructed, tested and direct costs estimated. Bananas were tested against a control open air drying system with the solar radiation, temperatures and moisture losses monitored. Both designs reduced drying times to less than two Cape Town winter days while open air drying was problematic, lasting up to one week. Direct cost of each dryer was under ZAR2000. It was therefore concluded that the designs are feasible and are now ready for redevelopment for commercial purposes.